Biocompatible and mechanically-reinforced tribopositive nanofiber mat for wearable and antifungal human kinetic-energy harvester based on wood-derived natural product. (1st June 2022) - Park, Dogun; Hong, Joo-Hyun; Choi, Daekyu; Kim, Donghyeun; Jung, Won Hee; Yoon, Sam S.; Kim, Ki Hyun; An, Seongpil
Abstract: Developing sustainable and environmentally friendly energy harvester is of great interest for various applications, especially for wearable and body-attachable self-powered electronics. Here, a biocompatible, mechanically durable, and sustainable wood-derived triboelectric nanogenerator (wood-TENG) is fabricated and applied as a human kinetic-energy harvester, along with an antifungal activity against athlete's foot. The wood-TENG is composed of the wood-derived natural product, i.e., the root bark of Ulmus davidiana var. japonica and the biocompatible polymer, i.e., polycaprolactone (PCL). The incorporation of U. davidiana var. japonica in nonwoven PCL nanofiber (NF) mat not only enhances the mechanical properties of the wood-TENG, but also increases the surface energy of the NF mat, resulting in the highest energy harvesting efficiency as compared to those of other bio-TENGs. Various physicochemical characterizations, including Fourier transform infrared (FTIR), Kelvin probe force microscopy (KPFM), etc., are conducted to explore the tribopositivity of the NF mat. Thanks to the enhanced triboelectricity, our wood-TENG can generate a maximum output voltage of 80 V and show stable cyclic energy harvesting performance during 100, 000 cycles. Graphical Abstract: ga1 Highlights: Biocompatible wood-derived triboelectric nanogenerator (wood-TENG) is fabricated. The wood-TENG is composed of Ulmus davidiana var. japonica and polycaprolactone. The wood-TENG has an antifungal activity against athlete's' foot. Energy harvesting performance and working principle of the wood-TENG are explored.